Threespine Stickleback in Lake Constance: The Ecology and Genomic Substrate of a Recent Invasion - Hudson, Cameron M.; Lucek, Kay; Marques, David A.; Alexander, Timothy J.; Moosmann, Marvin; Spaak, Piet; Seehausen, Ole; Matthews, Blake (Frontiers in Ecology and Evolution, 2021)
Invasive species can be powerful models for studying contemporary evolution in natural environments. As invading organisms often encounter new habitats during colonization, they will experience novel selection pressures. Threespine stickleback (Gasterosteus aculeatus complex) have recently colonized large parts of Switzerland and are invasive in Lake Constance. Introduced to several watersheds roughly 150 years ago, they spread across the Swiss Plateau (400-800 m a.s.l.), bringing three divergent hitherto allopatric lineages into secondary contact. As stickleback have colonized a variety of different habitat types during this recent range expansion, the Swiss system is a useful model for studying contemporary evolution with and without secondary contact. For example, in the Lake Constance region there has been rapid phenotypic and genetic divergence between a lake population and some stream populations. There is considerable phenotypic variation within the lake population, with individuals foraging in and occupying littoral, offshore pelagic, and profundal waters, the latter of which is a very unusual habitat for stickleback. Furthermore, adults from the lake population can reach up to three times the size of adults from the surrounding stream populations, and are large by comparison to populations globally. Here, we review the historical origins of the threespine stickleback in Switzerland, and the ecomorphological variation and genomic basis of its invasion in Lake Constance. We also outline the potential ecological impacts of this invasion, and highlight the interest for contemporary evolution studies.